Isolation and analysis of ribonucleic acids - King, Harry W S (Department of Medicine, 2020)
Ribonucleic acids are concentrated in certain parts of the cell. Separation of these parts usually precedes isolation of the ribonucleic acids they contain. This separation is accomplished by a process of cell fractionation (Mathias, 1966).